A bio-sustainable approach for reducing Eucalyptus tree-caused agricultural ecosystem hazards employing Trichoderma bio-sustained spores and mycorrhizal networks - Kabir, Md. Golam; Wang, Yonglong; Abuhena, Md.; Azim, Md. Faisal; Al-Rashid, Jubair; Rasul, Noorain Munim; Mandal, Dipa; Maitra, Pulak (Frontiers in Microbiology, 2023)
An accumulation of undecomposed exotic Eucalyptus leaves and the tree itself in crop-growing soil presents a significant ecological hazard due to its waxy coating and phenolic compounds, which take a long time to break down under normal conditions. It is desirable to investigate various fungi from an eco-friendly standpoint. In this study, spores of nine native Trichoderma strains were produced on wheat agar using a lactic acid-induced sporulation strategy (LAISS). Trichoderma biosustained-spores and Serendipita indica (SI) were then applied to a rice field with accumulated Euca-lyptus leaves under continuous ponding (CP) and alternate flooding and wetting conditions (AFW). Among the strains, TI04 (Trichoderma viride) and TI15 (Tricho-derma citrinoviride) showed faster (5 days) and massive sporulation (1.06-1.38×1011 CFU/g) in LAISS. In vitro, TI04 and TI15 biosustained on Eucalyptus leaves and improved rice seedling growth and SI infection in greenhouse conditions. In the rice-field experiment, Trichoderma-treatment had a threefold yield (percentage) in-crease from control, with TI04 (CP) rising by 30.79, TI04 (AFW) rising by 29.45, TI15 (CP) rising by 32.72, and TI15 (AFW) rising by 31.91, whereas unfilled grain yield was significantly decreased in all Trichoderma-treatment. Under AFW conditions, TI04 and TI15 showed a greater pH increase. Furthermore, TI04 and TI15 under AFW had higher water productivity (t ha-1 cm-1) of 0.0763 and 0.0791, respectively, and the highest rates (percentage) of SI colonization of 86.36 and 83.16, respectively. Ac-cording to the findings, LAISS-produced Trichoderma spores can be applied to break down persistent wastes and restore agricultural ecosystems through increased my-corrhizae networking.